Technology and Young Learners - Kastuhandani, Fidelis Chosa (LLT Journal: A Journal on Language and Language Teaching, 2014)
Nowadays, technology can be accessed by everyone easily, including young learners. This article discusses three things; the first is the discussion of what characteristics young learners have, the second discussion is about what kinds of technologies that could be integrated into classroom activities, and the third discussion is about how to weave ICT into young learners classroom setting. Employing ICT in teaching English to young learners, indeed, provides challenges for teachers to overcome. By far, the most useful resources in the classroom are the students themselves.